The influence of income levels on smartphone purchase behavior among Malaysian Gen Y - Zihao, Wang (2023)
This research explores the factors influencing smartphone purchasing behavior among Malaysian Generation Y, with a specific focus on income levels as a moderating variable. Despite existing research on smartphone purchasing behavior in Malaysia, particularly using the Theory of Planned Behavior (TPB), there remains a significant research gap regarding the impact of income levels on this relationship. This study aims to explore this overlooked factor, as income level may act as a moderating factor between product characteristics, social factor, and purchasing behavior. The study employed a deductive research approach, collecting primary data from 384 respondents using systematic random sampling. A self-administered online questionnaire comprising 44 items, including demographic information, was used. A pilot study was conducted to ensure the instrument's validity. Data analysis was performed using SPSS, applying multiple regression analysis. The results reveal that product features, brand familiarity, and peer influence are significant antecedents of smartphone purchasing behavior among Generation Y, with product attributes emerging as the strongest predictor. However, income levels moderate the impact of these factors on purchasing decisions. Specifically, while friends’ recommendations, brand associations, and product features strongly influence purchase behavior, their effects vary depending on the buyer's income level. Higher or lower income levels shape the extent to which these factors impact the final purchasing decision, underscoring the role of income in influencing consumer behavior within this demographic. The research findings highlight the importance of tailoring marketing strategies for Generation Y who are the largest demographic of smartphone consumers in Malaysia the study concludes with recommendations for businesses to enhance their marketing strategies and conduct further research to gain deeper insights into Generation Y's purchasing patterns and spending behaviour in the smartphone market